EDUKASI CUCI TANGAN PAKAI SABUN (CTPS) YANG BAIK DAN BENAR PADA SISWA PAUD - Utama, Deddy Alif; Faizah, Atyaf Umi (Buletin Udayana Mengabdi, 2024)
Pre-school age (4-6 years) is the initial age when children's motor skills develop. They are sometimes driven by activities that bring them into contact with sources of disease transmission in the environment. The government of the Republic of Indonesia is currently aggressively promoting healthy lifestyles as one way to overcome this problem. The Clean and Healthy Living Behavior Program (PHBS) was the initial step chosen, where one of the activities was washing hands with running water and using soap (CTPS). The aim of this activity is to increase the knowledge and skills of students, guardians, and teachers at PAUD Puspa North Ayula Village regarding hand washing activities using soap. This activity is carried out in several stages, namely: 1) providing a pre-test and post-test to measure participants' knowledge and skills; 2) conducting outreach to students (i), guardians, and teachers; and 3) ending with a practice activity on how to wash your hands properly and correctly. The results achieved in this community service activity were an increase in participants' knowledge regarding CTPS from pre-test to post-test by 46.7%, while in the practical aspect of CTPS there was an increase of 158.91%. This indicates that the educational activities have been successful, so it is hoped that the CTPS program will continue to be implemented by PAUD teachers every new academic year.